Perturbation of monoamine metabolism and enhanced fear responses in mice defective in the regeneration of tetrahydrobiopterin. Issue 2 (14th March 2022) - Miyajima, Katsuya; Sudo, Yusuke; Sanechika, Sho; Hara, Yoshitaka; Horiguchi, Mieko; Xu, Feng; Suzuki, Minori; Hara, Satoshi; Tanda, Koichi; Inoue, Ken‐ichi; Takada, Masahiko; Yoshioka, Nozomu; et al.
Abstract: Increasing evidence suggests the involvement of peripheral amino acid metabolism in the pathophysiology of neuropsychiatric disorders, whereas the molecular mechanisms are largely unknown. Tetrahydrobiopterin (BH4) is a cofactor for enzymes that catalyze phenylalanine metabolism, monoamine synthesis, nitric oxide production, and lipid metabolism. BH4 is synthesized from guanosine triphosphate and regenerated by quinonoid dihydropteridine reductase (QDPR), which catalyzes the reduction of quinonoid dihydrobiopterin. We analyzed Qdpr −/− mice to elucidate the physiological significance of the regeneration of BH4. We found that the Qdpr −/− mice exhibited mild hyperphenylalaninemia and monoamine deficiency in the brain, despite the presence of substantial amounts of BH4 in the liver and brain. Hyperphenylalaninemia was ameliorated by exogenously administered BH4, and dietary phenylalanine restriction was effective for restoring the decreased monoamine contents in the brain of the Qdpr −/− mice, suggesting that monoamine deficiency was caused by the secondary effect of hyperphenylalaninemia. Immunohistochemical analysis showed that QDPR was primarily distributed in oligodendrocytes but hardly detectable in monoaminergic neurons in the brain. Finally, we performed a behavioral assessment using a test battery. The Qdpr −/− mice exhibited enhanced fear responses after electrical foot shock. Taken together, our data suggest that the perturbation of BH4 metabolism should affect brain monoamine levels through alterations in peripheral amino acid metabolism, and might contribute to the development of anxiety‐related psychiatric disorders. Cover Image for this issue: https://doi.org/10.1111/jnc.15398 Abstract : Tetrahydrobiopterin (BH4) is a cofactor for enzymes that catalyse phenylalanine metabolism, monoamine synthesis, nitric oxide production, and lipid metabolism. BH4 is synthesized from guanosine triphosphate and regenerated by quinonoid dihydropteridine reductase (QDPR), which catalyses the reduction in quinonoid dihydrobiopterin. We analysed Qdpr −/− mice to elucidate the physiological significance of the regeneration of BH4. We found that the Qdpr −/− mice exhibited mild hyperphenylalaninemia and monoamine deficiency in the brain, despite the presence of substantial amounts of BH4 in the liver and brain. Hyperphenylalaninemia was ameliorated by exogenously administered BH4, and dietary phenylalanine restriction was effective for restoring the decreased monoamine contents in the brain of the Qdpr −/− mice, suggesting that monoamine deficiency was caused by the secondary effect of hyperphenylalaninemia. Immunohistochemical analysis showed that QDPR was primarily distributed in oligodendrocytes but hardly detectable in monoaminergic neurons in the brain. Finally, we performed a behavioural assessment using a test battery. The Qdpr −/− mice exhibited increased fear and anxiety after electrical foot shock. Taken together, our data suggest that the perturbation of BH4 metabolism should affect brain monoamine levels through alterations in peripheral amino acid metabolism, and might contribute to the development of anxiety‐related psychiatric disorders. Image content: Localization of QDPR in the brain. mmunofluorescence staining for TH (magenta) as a noradrenergic neuron marker and QDPR (green) in the locus coeruleus (LC). Scale bar, 100 μm. Cover Image for this issue: https://doi.org/10.1111/jnc.15398